Layanan referensi sebagai representasi perpustakaan perguruan tinggi - Putra, Irwin Pratama; Irawati, Indira (Jurnal Kajian Informasi dan Perpustakaan, 2018)
This study discusses whether the reference service owned by the Universitas Indonesia (UI) Library can be used as a representation of other college libraries. This representation can be seen based on user perception in the University of Indonesia Library of the reference service and also seen from the strategy undertaken by the University of Indonesia Library in improving the quality of their reference service. This research is a qualitative research using case study method. The results of this study indicate that the reference service Library University of Indonesia can be used as a representation of the library of universities, because the University of Indonesia Library managed to make their reference services become more active and more innovative by bringing various innovations in it to get closer to the user. In addition, users also express their opinions regarding reference services in the University of Indonesia Library, this will further strengthen the purpose of this research is a reference service as a representation of the University of Indonesia Library. It is expected that with the innovation made by UI Library to its reference service will make the reference service become the representation of the library itself especially from the user side, because the representation of the reference service is very important to realize the main purpose of university in Indonesia known as Tri Dharma Perguruan Tinggi is education, research and community service.